2014
DOI: 10.1002/cam4.252
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cyanine dyes for in vivo optical imaging of altered mitochondrial membrane potential in tumors

Abstract: Mitochondrial membrane potential (Δψm) alteration is an important target for cancer diagnosis. In this study, we designed a series of near-infrared fluorescent cationic cyanine dyes with varying alkyl chain lengths (IC7-1 derivatives) to provide diverse lipophilicities and serum albumin-binding rates, and we evaluated the usefulness of these derivatives for in vivo Δψm imaging. IC7-1 derivatives with side chains from methyl to hexyl (IC7-1-Me to IC7-1-He) were synthesized, and their optical properties were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…[39] Therefore,c ations with strong lipophilicity tend to move across the phospholipid bilayer of the inner membrane and accumulate inside the mitochondrial matrix at ar atio of more than 10:1 compared to other organelles,d riven by the potential gradient of the membrane. [31,41] Such fluorophores have been optimized and commercialized to adapt to chemical biology studies.F or example,t he MitoTracker series (1 and 2,S cheme 1A), [42] which possess overall positive charge across the lipophilic scaffolds,c an be easily taken up by the mitochondria of live cells.They possess ab road range of options regarding emission wavelength, while showing minimum staining of other organelles. [31,41] Such fluorophores have been optimized and commercialized to adapt to chemical biology studies.F or example,t he MitoTracker series (1 and 2,S cheme 1A), [42] which possess overall positive charge across the lipophilic scaffolds,c an be easily taken up by the mitochondria of live cells.They possess ab road range of options regarding emission wavelength, while showing minimum staining of other organelles.…”
Section: The General Methods To Design Mitafpsmentioning
confidence: 99%
“…[39] Therefore,c ations with strong lipophilicity tend to move across the phospholipid bilayer of the inner membrane and accumulate inside the mitochondrial matrix at ar atio of more than 10:1 compared to other organelles,d riven by the potential gradient of the membrane. [31,41] Such fluorophores have been optimized and commercialized to adapt to chemical biology studies.F or example,t he MitoTracker series (1 and 2,S cheme 1A), [42] which possess overall positive charge across the lipophilic scaffolds,c an be easily taken up by the mitochondria of live cells.They possess ab road range of options regarding emission wavelength, while showing minimum staining of other organelles. [31,41] Such fluorophores have been optimized and commercialized to adapt to chemical biology studies.F or example,t he MitoTracker series (1 and 2,S cheme 1A), [42] which possess overall positive charge across the lipophilic scaffolds,c an be easily taken up by the mitochondria of live cells.They possess ab road range of options regarding emission wavelength, while showing minimum staining of other organelles.…”
Section: The General Methods To Design Mitafpsmentioning
confidence: 99%
“…6571 Rhodamine- and cyanine-based cationic fluorophores have been extensively used as research tools as mitochondrial stains and for monitoring mitochondrial membrane potential, as discussed below, based on the extent of their total cellular uptake or the ratio of mitochondrial to cytosolic concentration of the cationic probe. 72–81 Small molecule heterocyclic cations were also used as vehicles to deliver other compounds to mitochondria. 8292 The heterocyclic cations have been conjugated with quinone, spin traps, or thiol-reactive moieties to specifically localize those compounds in cell mitochondria.…”
Section: Approaches To Target Compounds To Mitochondriamentioning
confidence: 99%
“…Moreover, it has been reported that drugs with preferential affinity towards binding site II show efficient photodynamic therapeutic applications . In order to use albumin as a tumor targeting carrier, a moderate binding between the protein and the drug is required . Then, along with the potency of drug‐target binding interactions measured by the K d , binding kinetics is undoubtedly an essential issue in drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In order to use albumin as at umor targeting carrier, am oderate binding between the protein and the drug is required. [3] Then, along with the potencyo fd rug-target binding interactions measured by the K d ,b inding kinetics is undoubtedly an essential issue in drug discovery.B oth residence time and association rate constant are important parameters for in vivo efficacy and safety of drugss ince they can help in understanding their mechanismso fa ction and structure-activity relationships. [4] Ag reat number of studies involving protein-dye interactions have been published so far [5] since the interesti nd eveloping new probes that can noncovalently bind proteins for their detection and sensingi sc onstantly growing.…”
Section: Introductionmentioning
confidence: 99%